Pemahaman Konsep Laju Reaksi Siswa SMA melalui Game Edukasi Berbasis Pendekatan Kontekstual - Rumahorbo, Shinta; Aznam, Nurfina; Anding, Imanuel (Jurnal Pendidikan dan Pengajaran, 2025)
Lack of utilization of learning media in the era of Technology that can facilitate students in the learning process, so that students feel less understanding of the concept of the material being studied. The study aims to create educational game media with a contextual approach to the reaction rate material to improve the understanding of high school students' concepts. The study uses the development of the 4D model. The study subjects comprised 2 media and material expert validations, 5 teachers, and 36 grade XI high school students. The data collection method uses Observation, questionnaires, and tests. The analysis technique uses a feasibility analysis with a Likert scale, an empirical test of questions with the Quest program, and an Analysis of game effectiveness using the SPSS Anova Test. The educational game media research results are valid in design, material, and language. The results of the practicality and readability tests obtained 92.26% and 85.28% in the very good category. The ANOVA test obtained a sign of less than 0.005 with the conclusion that the educational game media has a significant difference with a partial eta square of 0.41 in the very large category. The N Gain test showed a difference in the pretest and posttest of the three classes. The experimental class owned the most significant increase in N-Gain using educational games with a contextual approach. The study's conclusion shows that game media is valid, practical, and effective in improving students' conceptual understanding of chemistry subjects. This study implies that with educational games with a contextual approach, students can understand the material on chemical reaction rates well.